Controlled Multicenter Pilot Study of Urokinase – Heparin and Streptokinase in Deep Vein Thrombosis - van de Loo, J C W; Kriessmann, A; Trübestein, G; Knoch, K; de Swart, C A M; Asbeck, F; Marbet, G A; Schmitt, H E; Sewell, A F; Duckert, F; Theiss, W; Ritz, R (Thrombosis and Haemostasis, 1983)
Thirty-three patients with acute iliofemoral thrombosis were randomly assigned to three treatment groups in a pilot doseranging study of thrombolytic therapy in deep vein thrombosis. One group received tissue culture urokinase in a dose of 2,200 I.U./kg/hr, and a second group in a dose of 1,100 I.U./kg/hr following a loading dose of 4,400 I.U./kg given in ten min. Urokinase was administered for 12 hr periods, alternating with 12 hr periods of heparin. A third group received an initial dose of 250,0001.U. of streptokinase in 20 min, followed by 100,000 I.U./hr. Treatment of all patients continued for three days. At the end of this period little improvement, evaluated by “blinded” interpretation of pre- and post-treatment phlebograms, was found in five out of ten of the higher-dose urokinase patients, seven out of eleven of lower-dosage urokinase patients, and six out of ten of streptokinase patients. Optional treatment for another three days showed little further improvement of urokinase-patients and moderate further improvement in the streptokinase-patients. – Neither of the 2 dosage schemes at intermittent application of urokinase appeared to be advantageous. Urokinase treated patients experienced fewer adverse reactions.
Keywords: Urokinase; Streptokinase; Thrombolytic treatment; Deep venous thrombosis